(untitled) (Research, Society and Development, 2022)
The present study aimed to describe as main contributions that the nursing team brings physical recovery and emotional control of patients in the post-surgical moment. To respond to this objective, the Integrative Literature Review was adopted as a methodology. Going through six steps, identification of the theme, problem definition, elaboration of studies which was built from the acronym PICo, search in databases, selection of those with north through sample, and search strategies. From the acronym, the guiding question of the study was defined in the period: What is the contribution of the nursing team to the postoperative patient? The search in the databases through the crossing of descriptions, used as a filter carried out during the 5-year period of work, resulted in 11 articles included in the final sample. The results of the studies obtained showed that the nurse is a key and necessary part in the patient’s recovery from their preliminary conditions to the operational procedures performed, being ideal for the execution of an integral and genuine professional in view of the professional skills they have.